Influenza vaccine effectiveness estimates against influenza A(H3N2) and A(H1N1) pdm09 among children during school-based outbreaks in the 2016-2017 season in Beijing, China - Li Zhang; Wim van der Hoek; Thomas Krafft; Eva Pilot; Liselotte van Asten; Ge Lin; Shuangsheng Wu; Wei Duan; Peng Yang; Quanyi Wang (Taylor & Francis Group, 2020)
Background Since 2007, trivalent inactivated influenza vaccine (TIV) has been provided free-of-charge to primary, middle school and high school students in Beijing. However, there have been few school-based studies on influenza vaccine effectiveness (VE). In this report, we estimated influenza VE against laboratory-confirmed influenza illness among school children in Beijing, China during the 2016-2017 influenza season. Methods The VE of 2016-2017 TIV against laboratory-confirmed influenza virus infection among school-age children was assessed through a case-control design. Conditional logistic regression was conducted on matched case-control sets to estimate VE. The effect of prior vaccination on current VE was also examined. Results All 176 samples tested positive for influenza A virus with the positive rate of 55.5%. The average coverage rate of 2016-2017 TIV among students across the 37 schools was 30.6%. The fully adjusted VE of 2016-2017 TIV against laboratory-confirmed influenza was 69% (95% CI: 51 to 81): 60% (95% CI: −15 to 86) for influenza A(H1N1)pdm09 and 73% (95% CI: 52 to 84) for influenza A(H3N2). The overall VE for receipt of 2015-2016 vaccination only, 2016-2017 vaccination only, and vaccinations in both seasons was 46% (95% CI: −5 to 72), 77% (95% CI: 58 to 87), and 57% (95%CI: 17 to 78), respectively. Conclusions Our study during school outbreaks found that VE of 2016-2017 TIV was moderate against influenza A(H3N2) as well as A(H1N1)pdm09 viruses.